INTERDISCIPLINARY APPROACH TO THE ECONOMIC ENTITIES’ SUSTAINABILITY STUDY - MARGARITA Melnik (Учёт. Анализ. Аудит)
The article describes the major stages and the evolution of the research in the sphere of sustainability of economic entities (units), defines the relationship between sustainable development and changes in the key elements of an organization’s business processes, identifies the peculiarities of sustainable development of economic units belonging to different levels and their interdependence. The author analyses the basic approaches to giving definitions of sustainability in political economy, system analysis and in applied economics, singles out their similarities and objective differences. The article mainly focuses on defining sustainability ofa business entity as a primary element of national economy. It compares major features and factors of ensuring the sustainability including the consistency of strategic changes in different elements of production and business processes, monitoring of changes in close and distant environment of an economic entity, using the best practices of business partners, the analysis of support of long-term innovations by current changes which ensure the elimination of losses and sustainable cost reduction on the basis of resource-efficient development. Special emphasis is put on integration factors of ensuring the sustainability. The author proves that to ensure the sustainability consistent changes resulting in a synergistic effect are required.